Analytical evaluation of nine serological assays for diagnosis of syphilis - Malm, K.; Andersson, S.; Fredlund, H.; Norrgren, H.; Biague, A.; Månsson, F.; Ballard, R.; Unemo, M. (Journal of the European Academy of Dermatology and Venereology, 2015)
Background The diagnosis of syphilis is most frequently dependent on antibody detection with serological assays. Assays for both treponemal and non‐treponemal antibodies are needed to provide a sensitive and specific diagnosis. For decades, a first screening has been done with non‐treponemal assays, followed by treponemal. However, in recent years, following laboratory automation, the reverse sequence screening algorithms have been developed, using a treponemal assay as the initial screening test. Objective To evaluate serological assays for treponemal and non‐treponemal antibodies, to use in reverse algorithm screening of syphilis. Material and methods Six treponemal assays (one IgM‐specific assay), two non‐treponemal assays and one novel dual point‐of‐care (POC) assay for serological diagnosis of syphilis were evaluated. Serum samples from Guinea‐Bissau and Sweden were examined, as well as two performance panels and samples from blood donors. Sensitivity and specificity were calculated for each assay, using different assays as gold standard test. Results The Macro‐Vue RPR Card test was the most sensitive non‐treponemal test and the TrepSure Anti‐Treponema EIA Screen and the SeroDia TP‐PA were the most sensitive and specific treponemal assays. Among the automated assays, both the Liaison Treponema Screen and Architect Syphilis TP showed high sensitivity, however, the former had clearly higher specificity. Conclusions In resourced settings, where the reverse sequence algorithm is preferred for screening, an automated treponemal immunoassay for initial screening subsequently followed by the TrepSure test or TP‐PA assay as a second treponemal assay appear highly effective. Finally, a quantitative highly sensitive non‐treponemal assay, e.g. the Macro‐Vue RPR Card test, could then be used as a supplementary test to evaluate activity of the syphilis infection.